1973
DOI: 10.1083/jcb.56.2.580
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND CHARACTERIZATION OF MITOCHONDRIAL DNA FROM DROSOPHILA MELANOGASTER

Abstract: A B S T R A C TMitochondrial DNA (MtDNA) with a neutral buoyant density of 1.681 g/cm a has been isolated from unfertilized eggs of Drosophila mdanogaster. This DNA is a circular molecule with an average length of 5.3 /~m; it reassociates with a low Coil~2 after denaturation, and in alkaline isopycnic centrifugation it separates into strands differing in density by 0.005 g/cm 3 MtDNA isolated from purified mitochondria of unfertilized eggs or from total larval DNA melts with three distinct thermal transitions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2

Year Published

1973
1973
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 30 publications
2
14
2
Order By: Relevance
“…Evidence has been presented that circular molecules of approximately this size represent the mitochondriM DNA (mtDNA) of D. melanogaster (Polan et al, 1973 ;Bultmann and Laird, 1973). The abundance of these circular molecules in the present preparations and their interpretation as mtDNA is in agreement with the finding that approximately one-hMf of the DNA of unfertilized eggs of D. melanogaster is mitochondrial (Polun et al, 1973).…”
Section: Resultssupporting
confidence: 90%
“…Evidence has been presented that circular molecules of approximately this size represent the mitochondriM DNA (mtDNA) of D. melanogaster (Polan et al, 1973 ;Bultmann and Laird, 1973). The abundance of these circular molecules in the present preparations and their interpretation as mtDNA is in agreement with the finding that approximately one-hMf of the DNA of unfertilized eggs of D. melanogaster is mitochondrial (Polun et al, 1973).…”
Section: Resultssupporting
confidence: 90%
“…melanogaster mtDNA reported previously (3,23,24,32). When these mtDNA preparations were centrifuged to equilibrium in cesium chloride-ethidium bromide gradients, two visible bands were formed.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) of Drosophila melanogaster is in the form of circular molecules with a similar contour length of about 6.2 tzm (mol wt = 12.35 x 106 daltons) (3,9,10,23,24,32). The findings of triphasic (24) and biphasic (3) hyperchromic changes in this DNA upon heating indicated that a portion of it contained a distinctly higher content of adeninethymine than the remainder.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this report, the methods used to purify mitochondria from Drosophila (28,35) were modified to prepare DNA from Wolbachia in quantities that could be visualized by ethidium bromide staining of agarose gels. Around 5 ml of adult flies (about 1,000) was collected and then homogenized in buffer as previously described (9), except without Lubrol (90 mM KCl, 55 mM CaCl 2 , 15 mM MgSO 4 , 30 mM NaCl, 250 mM sucrose) using a Dounce tissue grinder (Wheaton, Millville, N.J.).…”
Section: Methodsmentioning
confidence: 99%